Neratinib and entinostat combine to rapidly reduce the expression of K-RAS, N-RAS, Gαq and Gα11 and kill uveal melanoma cells. Issue 5 (4th May 2019) - Booth, Laurence; Roberts, Jane L.; Sander, Cindy; Lalani, Alshad S.; Kirkwood, John M.; Hancock, John F.; Poklepovic, Andrew; Dent, Paul
ABSTRACT: There is no efficacious standard of care therapy for uveal melanoma. Unlike cutaneous disease, uveal melanoma does not exhibit RAS mutations but instead contains mutations with ~90% penetrance in either Gαq or Gα11 . Previously we demonstrated that neratinib caused ERBB1/2/4 and RAS internalization into autolysosomes which resulted in their proteolytic degradation. In PDX isolates of uveal melanoma, neratinib caused the internalization and degradation of Gαq and Gα11 in parallel with ERBB1 breakdown. These effects were enhanced by the HDAC inhibitor entinostat. Similar data were obtained using GFP/RFP tagged forms of K-RAS V12. Down regulation of Gαq and Gα11 expression and RAS-GFP/RFP fluorescence required Beclin1 and ATG5. The [neratinib + entinostat] combination engaged multiple pathways to mediate killing. One was from ROS-dependent activation of ATM via AMPK-ULK1-ATG13-Beclin1/ATG5. Another pathway was from CD95 via caspase 8-RIP1/RIP3. A third was from reduced expression of HSP70, HSP90, HDAC6 and phosphorylation of eIF2α. Downstream of the mitochondrion both caspase 9 and AIF played roles in tumor cell execution. Knock down of ATM/AMPK/ULK-1 prevented ATG13 phosphorylation and degradation of RAS and Gα proteins. Over-expression of activated mTOR prevented ATG13 phosphorylation and suppressed killing. Knock down of eIF2α maintained BCL-XL and MCL-1 expression. Within 6h, [neratinib + entinostat] reduced the expression of the immunology biomarkers PD-L1, ODC, IDO-1 and enhanced MHCA levels. Our data demonstrate that [neratinib + entinostat] down-regulates oncogenic RAS and the two key oncogenic drivers present in most uveal melanoma patients and causes a multifactorial form of killing via mitochondrial dysfunction and toxic autophagy. Abbreviations : ERK: extracellular regulated kinase; PI3K: phosphatidyl inositol 3 kinase; ca: constitutively active; dn: dominant negative; ER: endoplasmic reticulum; AIF: apoptosis inducing factor; AMPK: AMP-dependent protein kinase; mTOR: mammalian target of rapamycin; JAK: Janus Kinase; STAT: Signal Transducers and Activators of Transcription; MAPK: mitogen activated protein kinase; PTEN: phosphatase and tensin homologue on chromosome ten; ROS: reactive oxygen species; CMV: empty vector plasmid or virus; si: small interfering; SCR: scrambled; IP: immunoprecipitation; VEH: vehicle; HDAC: histone deacetylase.